Study of the Size and Morphology of Aggregates Formed by Pentaethylene Glycol Monooctyl Ether (C8eo5) in N-Heptane - Guerra-Benavente, I (Elsevier B.V., 2012)
The size and morphology adopted by aggregates formed by a non-ionic surfactant, pentaethylene glycol monooctyl ether (C8EO5) in deuterated heptane were studied in detail. Self-diffusion coefficients were estimated by means of 1H-NMR DOSY measurements. Considerable differences in the diffusion coefficients were found for samples with concentrations below and above the critical aggregate concentration - CAC - of the surfactant. The difference is attributed to the presence of aggregates. No significant change in the diffusion coefficient was observed by increasing surfactant concentration; therefore the aggregates exhibit a homogeneous size distribution. Through the diffusion coefficient, a study of the possible size and shape of these aggregates was made. Four different structures were considered: prolate and oblate ellipse, sphere and cylinder, for which structural parameters were calculated using the general Stokes-Einstein equation. The results allow delimiting the size for the possible configurations that C8EO5 aggregates exhibit in heptane. © 2012 Elsevier B.V.